INNOVATION IN THE EUROPEAN UNION - VLADIMIR-CODRIN IONESCU; VIOREL CORNESCU (Global Economic Observer)
In the contemporary knowledge-based society, innovation, as a vector used for the application and promotion of inventions and innovations, is one of the main sources used for obtaining a sustainable competitive advantage. The present paper points out the main directions which the European Commission aims to develop in the sphere of innovation, within the context of the Initiative: “A Union of Innovation”, which is part of the Europe 2020 Strategy. The paper analyses the performances accomplished by the EU states in the area of innovation while developing an international perspective that may represent the starting point in identifying solutions whereby the EU could reduce the gaps that exist in relation to the main international competitors, i.e. South Korea, USA and Japan.